Future Trends In Halal Food: How Innovative Islamic Business Models Are Redefining The Indonesian Market - Qizwini, Jimmi; Purnama, Diki Gita (Journal Of Middle East and Islamic Studies, 2024)
Indonesia, a leading actor in the global halal food market, is undergoing significant transformations driven by the adoption of innovative Islamic business models. These models, which seamlessly integrate Islamic ethical principles with contemporary market forces, are fundamentally reshaping the structural and operational landscape of Indonesia’s halal food industry. This study aims to systematically investigate emerging trends, evaluate the impact of these pioneering business models, and provide a comprehensive analysis of their influence on consumer preferences and industry practices. Through a descriptive literature review, the research synthesizes insights from academic discourse and case studies to offer a thorough understanding of these developments. The findings demonstrate that businesses such as Mubarokfood and Sicadas.com serve as exemplary cases of successfully integrating Islamic values with modern business strategies, achieving competitive advantages in the market. These examples underscore the potential for Islamic business models to align religious principles with evolving consumer behavior and global market demands. The study concludes that these innovative models are crucial in redefining Indonesia’s halal food sector, offering valuable insights for businesses, policymakers, and scholars seeking to align Islamic principles with the complexities of an increasingly globalized market, ensuring sustainable growth and competitiveness.